Development of a highly stable picosecond time‐resolved Raman spectrometer near Fourier‐transform limit with a femtosecond light source. (19th August 2021) - Tokita, Tsukasa; Takaya, Tomohisa; Iwata, Koichi
Abstract: Picosecond time‐resolved Raman spectroscopy is an experimental method effective for studying the structure and dynamics of short‐lived transient species. Spectral resolution of less than 10 cm −1 and high stability of the laser light source are both critically important for extracting detailed information on the structure and dynamics of the transient species from the observed picosecond time‐resolved Raman spectra. However, it is often technically challenging to obtain stable picosecond pulses that have a spectral width of 10 cm −1 or smaller, which is only achieved if the time‐energy product of a light pulse is close to the Fourier‐transform limit, from a picosecond light source. We present a new scheme for a picosecond time‐resolved Raman spectrometer with a stable femtosecond laser as its light source. Femtosecond light pulses from the laser are successfully converted to stable picosecond light pulses with a volume‐grating notch filter. The spectral and temporal widths of the prepared picosecond pulse are 6.0 cm −1 and 3.2 ps, respectively, close to the Gaussian Fourier‐transform limit. The vibrational cooling dynamics of S1 trans ‐stilbene prepared with the photoexcitation at 316 and 266 nm has been observed with the newly developed picosecond time‐resolved Raman spectrometer, demonstrating a high capability of the proposed method. Abstract : A picosecond time‐resolved Raman spectrometer is constructed with a stable femtosecond light source. The femtosecond light pulses are successfully converted to picosecond pulses with a volume‐grating notch filter. The spectral and temporal widths of the prepared picosecond pulse are 6.0 cm −1 and 3.2 ps, respectively, close to the Gaussian Fourier‐transform limit.